Agents of Change: A Critical Analysis of Governing Actors in Alberta’s 2030 Higher Education Reform Plan - Younes, Marwa (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2025)
Every province and territory in Canada has the authority to oversee higher education policies. In recent provincial and federal policy reforms, neoliberalism and academic capitalism have been gaining influence in Canadian higher education. This particularly applies to the policy reform plan Alberta 2030: Building Skills for Jobs, which was issued to develop higher education in the province. This paper critically analyzes the recent 10-year plan to reform Alberta’s higher education by combining Bacchi’s (2009) ‘What is the Problem Represented’ (WPR) approach and Chou et al.’s (2017) multi-actor framework. The purpose of this analysis is to provide insight into the actors and agendas affected by market-driven ideologies (i.e., neoliberalism and academic capitalism) on higher education policy in Alberta, Canada, with a focus on the abovementioned reform plan. The analysis underscores that the shift toward a profit-oriented approach challenges the traditional notion of higher education as a public good. This paper also discusses the implications of the reform plan and recommendations for its application.